2010
DOI: 10.1590/s0100-29452010005000117
|View full text |Cite
|
Sign up to set email alerts
|

Composição centesimal e de minerais de casca e polpa de manga (Mangifera indica L.) cv. Tommy Atkins

Abstract: RESUMO-O Brasil produz cerca de 140 milhões de toneladas de alimento por ano; entretanto, a fome ainda é um dos maiores problemas enfrentados por grande parte da sua população. O aproveitamento integral de alimentos é uma alternativa para suprir as necessidades nutricionais e contribuir para reduzir o lixo orgâni-co. Nesse sentido, cascas, talos, sementes e outras partes, tradicionalmente não utilizadas como alimentos, podem ser incorporadas na dieta alimentar. Estudos revelam que cascas de muitas hortifrutíco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
22

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 12 publications
1
9
1
22
Order By: Relevance
“…The correlations between total phenolic compounds and antioxidant capacity were strong and significant for ABTS and FRAP results. Probably, phenolics are the main compounds responsible for the antioxidant capacity of baru fruit, mostly gallic acid, catechin and ferulic acid (Lemos et al, 2012), and tannin (Marin et al, 2009), as reported for baru almond. Furthermore, the significant correlations between the ABTS and FRAP, and between the FRAP and DPPH assays, suggest that the FRAP may be the most suitable method to assess the antioxidant capacity in these food matrices (Table 3).…”
Section: Samplementioning
confidence: 76%
“…The correlations between total phenolic compounds and antioxidant capacity were strong and significant for ABTS and FRAP results. Probably, phenolics are the main compounds responsible for the antioxidant capacity of baru fruit, mostly gallic acid, catechin and ferulic acid (Lemos et al, 2012), and tannin (Marin et al, 2009), as reported for baru almond. Furthermore, the significant correlations between the ABTS and FRAP, and between the FRAP and DPPH assays, suggest that the FRAP may be the most suitable method to assess the antioxidant capacity in these food matrices (Table 3).…”
Section: Samplementioning
confidence: 76%
“…Mango (Mangifera indica L.) is one of the most produced fruits in the world, being highly appreciated for its taste, color and aroma, and has many nutrients and short period of storage. In Brazil, the Northeast region is the main area of production and exportation, and the variety Tommy Atkins is one of the most popular (Marques et al, 2010;Sivakumar et al, 2011). Since it is highly perishable, technologies of conservation, such as drying, become interesting.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo estos residuos orgánicos representan un contenido nutritivo muy interesante, como es el caso de la cáscara de mango, la cual posee un contenido de proteína, almidón y fibra mayor que en la pulpa, además de contener magnesio, fosforo, sodio, potasio y calcio (MARQUES et al, 2010); la semilla se caracteriza por su contenido de proteínas, cenizas, fibra, carbohidratos, vitaminas, minerales y grasas (SUMAYA et al, 2012).…”
Section: Introductionunclassified